Climate of Diversity in Education as A Step to Cultivating Multicultural Attitudes in Educational Units - Fauzi, M. Asif Nur; Barory, Chulil (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This research was motivated by the discovery of several disparities and gaps in the educational climate in schools, especially in the aspect of students' awareness in responding to the diversity that exists in schools, so that gaps still appear in their interactions. The emergence of these gaps has the potential to increase cases of bullying among students. This is supported by the lack of responsiveness of school management in minimizing the gaps that occur so that innovation is needed in educational quality standards regarding the culture of diversity to support the success of the project to strengthen the profile of Pancasila students which is implemented. The research method used is a qualitative method with a library approach by reviewing several literatures that are relevant to this field of study. Based on the results of studies conducted, fostering a climate of diversity has an important role in efforts to foster an attitude of multiculturalism in educational units, namely the growth of positive communication in student interactions both in the school environment and in community life.